2017
DOI: 10.1016/j.brachy.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Visual acuity, oncologic, and toxicity outcomes with 103 Pd vs. 125 I plaque treatment for choroidal melanoma

Abstract: PURPOSE To evaluate outcomes of choroidal melanoma patients treated with 125I or 103Pd plaque brachytherapy. METHODS AND MATERIALS From 1993 to 2012, our institution treated 160 patients with 103Pd (56.1%) and 125 patients with 125I (43.9%) plaque brachytherapy. Tumor outcomes, visual acuity (VA), and toxicity were compared. Multivariate analyses (MVAs) and propensity score analysis were used to help address differences in baseline characteristics. RESULTS Median followup was longer for 125I patients, 52.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In the case of DEF of gold and gadolinium nano-particles in the brachytherapy, some paper has been published [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The studies show that for low energy sources, DEF of nanoparticles is higher than high energy sources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of DEF of gold and gadolinium nano-particles in the brachytherapy, some paper has been published [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The studies show that for low energy sources, DEF of nanoparticles is higher than high energy sources.…”
Section: Resultsmentioning
confidence: 99%
“…Different brachytherapy sources with own design have been studied utilizing Monte Carlo (MC) simulation and experimentally by different dosimeters [1][2][3][4][5][6][7]. Among the sources, 125 I seed also has designed and used to cancerous tissue treatment [8][9][10][11][12]. Villagas et al [9] conducted a study to characterize the magnitude of the spread in specific energy deposition per cell and reported increasing in micro-dosimetric value with decreasing target size and decreasing energy of the radiation quality.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of visual acuity: Marconi et al 44 noted that after 106 Ru plaque brachytherapy, 56% of patients had visual acuity of 20/25 initially, out of which more than half stayed with 20/40. Patel et al 45 compared 103 Pd with 125 I and found that >20/40 visual acuity was noted in 65% with 103 Pd versus 30% with 125 I. Papakostas et al 46 noted visual acuity of ⩾20/200 in 8.7% patients and counting fingers in 22% patients after proton beam radiotherapy. In our study, we noted excellent median visual acuity of 20/32 with 103 Pd plaque brachytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Head-to-head studies between iodine-135 and palladium-103 plaque brachytherapies are limited but it appears plaque brachytherapy delivered by either isotope has excellent overall survival and globe salvage rates. palladium-103 may demonstrate lower rates of radiation retinopathy [88]. In theoretical models using COMS plaques, cesium-131 may have the most uniform dose distribution but cesium plaque brachytherapy remains relatively uncommon [89].…”
Section: Plaque Brachytherapymentioning
confidence: 99%